Ukrainian Naval history as a component of the maritime code of the nation - Kalinichenko, Oleksandr O.; Yelesina, Maryna O.; Smyrynska, Nataliia B.; Syniavska, Olena O.; Leonova, Halyna O. (Linguistics and Culture Review, 2021)
This study is based on the information from different textbooks and manuals on the Naval and Navigation History. The Ukrainian publications on the history of navigation and naval history of Ukraine intended for teaching this subject in higher educational institutions are considered. The primary purposes of this study are: firstly, the emphasis is on the argumentation and reliability of historical constructions depending on the maritime professionalism of the researcher; secondly, the visualisation of historical material is presented clearly in the form of both photographs and relevant informative tables, which facilitate the perception of information, and in some cases replace a large number of narrative texts; thirdly, the author’s version of the structuring of the naval history of Ukraine was developed in tabular form. The study uses the statistical, chronological, and comparative approaches. As results, several tables and visual information were compiled, which could replace descriptive verbal historical texts. The connection between the national history of navigation and the Maritime Code of the Nation is established. The conclusion on the security of the state from the maritime threats was made due to the motivation of its defenders due to the professional study of the naval history of Ukraine.